Pendampingan Kemasan Pembuatan Bakso Berbahan Baku Sagu, Ikan Gastor, dan Rusa di Kampung Kaliki Merauke - Rizal, Abdul; Adrianus, Adrianus; Witdarko, Yus; Yusuf, Mani; Anwar, Anwar (Journal Of Human And Education (JAHE), 2024)
Kaliki Village, located in Merauke, Papua, has abundant natural resource potential but has not been utilized optimally in the economic activities of the local community. One of the products that can be developed is meatballs made from sago, Gastor fish and deer, which are abundant local resources in the area. This research aims to provide assistance to the people of Kaliki Village in making meatballs made from sago, Gastor fish and deer, as well as in packaging techniques that comply with quality standards and market appeal. It is hoped that this assistance can increase the added value of products and introduce local products to a wider range of consumers. The methods used are training, technical guidance, and direct supervision of the production and product packaging processes. The results of this activity show that the people of Kaliki Village can develop meatball products using local raw materials which have the potential to become superior products with improved packaging quality and better